Missed meal boluses and poorer glycemic control impact on neurocognitive function may be associated with white matter integrity in adolescents with type 1 diabetes - Litmanovitch, Edna; Geva, Ronny; Leshem, Avital; Lezinger, Mirit; Heyman, Eli; Gidron, Maor; Yarmolovsky, Jessica; Sasson, Efrat; Tal, Sigal; Rachmiel, Marianna (Frontiers in Endocrinology, 2023)
Background: The notion that pediatric type 1 diabetes impacts brain function and structure at early life is of major concern. Neurological manifestations, including neurocognitive and behavioral symptoms, may be present from childhood, initially mild and undetectable in daily life. Despite intensive management and technological therapeutic interventions, most pediatric patients still do not achieve glycemic control goals of HbA1c<7.5%, and one of the most common causes for such poor control as well as the frequent transient hyperglycemic episodes may be their lifestyle, including missed meal boluses. Objective: to assess the association between specific neurocognitive accomplishments, including learning and memory, inhibition ability learning and verbal memory and semantic memory, during meals with and without blousing, with correlation to Diffusion Tensor Imaging measurements of major related tracts, and glycemic control, among adolescents with type 1 diabetes compared with their healthy siblings of similar age. Study design and methods: a case-controlled study that included 12- to18-year-old patients with type 1 diabetes (N=17, 8 males, diabetes duration of 6.53±4.1 years) and their healthy siblings (N=13). All were hospitalized for 30 hours for continuous glucose monitoring and repeated neurocognitive tests as a function of missed or appropriate pre meal bolus. This situation was mimicked by controlled/patient blinded manipulation of pre-meal insulin administration to enable capillary glucose of 240+ mg/dl versus 180- mg/dl 2 hours after similar meals, at similar time. The diabetes team randomly and blindly manipulated post-lunch glucose levels by injecting subcutaneously either rapid-acting insulin or 0.9%NaCl solution, before lunch. A specific neurocognitive test battery was performed twice, after each manipulation. Its results were compared. Additional neurocognitive tasks were performed during hospitalization without insulin manipulation. Participants underwent brain imaging, including diffusion tension imaging and tractography. Results: Significant association was demonstrated between glycemic control and performance in the domains of executive functions, inhibition ability, learning and verbal memory and semantic memory. inhibition ability related specifically to food management. Poorer glycemic control (˃8.3%) associated with poorer reaction time performance Conclusions These findings highlight possible compromise of brain networks responsible for learning, memory, and controlled reactivity to food in poorly controlled adolescents with type 1 diabetes.